Conformational stability and vibrational study of phenylacetyl chloride. (27th July 2015) - Tao, Yaping; Han, Ligang; Li, Xiaofeng; Han, Yunxia; Liu, Zhaojun
<x xml:space="preserve">Abstract</x> The Fourier transform infrared spectroscopy and Fourier transform Raman spectra of phenylacetyl chloride were recorded and analyzed in the range 3500–400 and 3500–200 cm−1 at room temperature, respectively. In order to obtain the structural information and conformational stabilities, a potential energy surface scan for internal rotation was carried out at the B3LYP/6‐31G(d) level. The potential energy surface reveals that the title compound has two minimal conformers (A and B). The optimized geometries, structural parameters, stabilities, energies, thermodynamic parameters, vibrational wavenumbers, infrared intensities, and Raman activities for the two conformers (A and B) have been obtained by employing B3LYP and MP2 calculations with 6‐311++G (d, p) basis sets. The conformational energy difference between A and B is very small, indicating that the B conformer coexists with the A conformer. The detailed vibrational assignments of vibrational spectra of each conformer have been made on the basis of the potential energy distributions analysis. The highest occupied molecular orbital–lowest unoccupied molecular orbital energy gap and molecular electrostatic potential of the two conformers have been also calculated for comparison of their chemical activities. Copyright © 2015 John Wiley & Sons, Ltd.